Choline chloride (ChCl) and monosodium glutamate (MSG)-based green solvents from optimized cactus malic acid for biomass delignification. (November 2017) - Yiin, Chung Loong; Quitain, Armando T.; Yusup, Suzana; Uemura, Yoshimitsu; Sasaki, Mitsuru; Kida, Tetsuya
Graphical abstract: Highlights: Malic acid was extracted from cactus and used as hydrogen bond donor. RSM was used for optimization of microwave-hydrothermal extraction. Hydrogen bonding of green solvents was evidenced by the shifts in peaks. The green solvents demonstrated promising and comparable delignification efficiency. Delignified biomass showed enhanced digestibility and thermal degradability. Abstract: This work aimed to develop an efficient microwave-hydrothermal (MH) extraction of malic acid from abundant natural cactus as hydrogen bond donor (HBD) whereby the concentration was optimized using response surface methodology. The ideal process conditions were found to be at a solvent-to-feed ratio of 0.008, 120 °C and 20 min with 1.0 g of oxidant, H2 O2 . Next generation environment-friendly solvents, low transition temperature mixtures (LTTMs) were synthesized from cactus malic acid with choline chloride (ChCl) and monosodium glutamate (MSG) as hydrogen bond acceptors (HBAs). The hydrogen-bonding interactions between the starting materials were determined. The efficiency of the LTTMs in removing lignin from oil palm biomass residues, empty fruit bunch (EFB) was also evaluated. The removal of amorphous hemicellulose and lignin after the pretreatment process resulted in an enhanced digestibility and thermal degradability of biomass.